The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1097/aog.0b013e318231934c
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Postpartum Preeclampsia and Eclampsia

Abstract: One week after discharge appears to be a critical period for the development of postpartum eclampsia. Education about the possibility of delayed postpartum preeclampsia and eclampsia should occur after delivery, whether or not patients develop hypertensive disease before discharge from the hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(63 citation statements)
references
References 12 publications
1
56
0
1
Order By: Relevance
“…This includes late postpartum eclampsia that may occur up to 4 to 6 weeks postpartum and that accounts for 15% of eclampsia cases without antepartum-associated diagnosis of hypertension. 21 Overall, a stepwise approach to the management of the patient with eclampsia includes (1) maternal support of vital functions; (2) control of seizure and prevention of recurrent seizures; (3) correction of maternal hypoxemia and/or acidemia; (4) control of severe hypertension to a safe range; and (5) consideration for determining timing and route of delivery. 22 Initial pharmacotherapy intervention is aimed toward reducing perinatal morbidity through seizure prophylaxis when severe features of preeclampsia manifest.…”
Section: Organ System Effects Of Hypertensive Disorders Of Pregnancymentioning
confidence: 99%
“…This includes late postpartum eclampsia that may occur up to 4 to 6 weeks postpartum and that accounts for 15% of eclampsia cases without antepartum-associated diagnosis of hypertension. 21 Overall, a stepwise approach to the management of the patient with eclampsia includes (1) maternal support of vital functions; (2) control of seizure and prevention of recurrent seizures; (3) correction of maternal hypoxemia and/or acidemia; (4) control of severe hypertension to a safe range; and (5) consideration for determining timing and route of delivery. 22 Initial pharmacotherapy intervention is aimed toward reducing perinatal morbidity through seizure prophylaxis when severe features of preeclampsia manifest.…”
Section: Organ System Effects Of Hypertensive Disorders Of Pregnancymentioning
confidence: 99%
“…Sometimes, preeclampsia can first manifest in the postpartum period, either after a pregnancy complicated by gestational hypertension, preexisting hypertension, or more rarely after a normotensive pregnancy [413]. Postpartum preeclampsia (PPPE) has been most commonly defined in the literature as a systolic blood pressure (SBP) ≥140 mmHg and/or diastolic blood pressure (DBP) ≥90 mmHg on at least two occasions, 4h apart and presenting more than 48h after delivery and before 6 weeks postpartum, without the need of a proteinuria [68, 11, 14, 15]. The majority of studies of PPPE include women with pregnancies complicated by hypertension or preeclampsia [68].…”
Section: Introductionmentioning
confidence: 99%
“…Postpartum preeclampsia (PPPE) has been most commonly defined in the literature as a systolic blood pressure (SBP) ≥140 mmHg and/or diastolic blood pressure (DBP) ≥90 mmHg on at least two occasions, 4h apart and presenting more than 48h after delivery and before 6 weeks postpartum, without the need of a proteinuria [68, 11, 14, 15]. The majority of studies of PPPE include women with pregnancies complicated by hypertension or preeclampsia [68]. A study of PPPE after normotensive pregnancy found that advanced maternal age (> 40 years old), Hispanic ethnicity, Black race, obesity and a history of gestational diabetes during the index pregnancy are risk factors for PPPE [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are many women diagnosed with a postpartum hypertensive disorder that had no antepartum or intrapartum issues with elevated blood pressure. 2,3 Antenatal management and delivery timing for pregnancies complicated by hypertension have been a frequent focus of clinical research, but there is no evidence-based standard for postpartum surveillance that might prevent postpartum hypertension. 4,5 …”
Section: Introductionmentioning
confidence: 99%
“…This data will add to the existing literature that has identified the complications associated with postpartum hypertension by readmission data. 3 Women presenting to an ED during the postpartum period represent a population of women whose needs are not being met by our current system. Given the potentially severe complications associated with postpartum hypertension, it is important that we learn more about the symptoms and characteristics that might better predict the complication of hypertension.…”
Section: Introductionmentioning
confidence: 99%